PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP PEMBANGUNAN DAERAH DI PROPINSI NUSA TENGGARA TIMUR - Yuniarti Reny Renggo (Yayasan Akrab Pekanbaru, 2019)
This study aims to analyze the effect of Regional Original Income (PAD), General Allocation Funds (DAU) and Special Allocation Funds (DAK) in improving regional development seen from two indicators, namely economic indicators (Economic Growth) and social indicators (Human Development Index or HDI). The analytical tool used in this study is Panel Data Regression Analysis from 2013 to 2016 at 21 municipal districts in East Nusa Tenggara Province. Viewed from the Economic Growth, the study showed that PAD, DAU and DAK have significant impact on regional development. However, from the social indicators perspective, the Human Development Index is only influenced by PAD and DAK, in which PAD decreases HDI; and DAK increases the HDI.